2015
DOI: 10.1111/ggi.12427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resistance training using bodyweight in the elderly: Comparison of resistance exercise movement between slow and normal speed movement

Abstract: The intervention program using only own bodyweight that comprised resistance exercise with slow movement and plyometric exercise can improve physical function in the elderly, even with single sets for each exercise. However, there was no enhanced muscle hypertrophic effect. Further attempts, such as increasing performing multiple sets, would be required to induce muscle hypertrophy. Geriatr Gerontol Int 2015; 15: 1270-1277.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 31 publications
1
36
1
Order By: Relevance
“…Although the present study's findings showed that SRT‐BW is effective for increasing muscle mass, Watanabe et al reported that resistance training using body weight with slow speed movement and tonic force generation (3‐second eccentric, 3‐second concentric, and 1‐second isometric actions with no rest between each repetition) improved physical function and strength but not muscle mass. Holm et al reported that even with low‐load resistance training (15.5% of one repetition maximum), a long total contraction time is related to the activation of motor units, which increases muscle size and strength.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Although the present study's findings showed that SRT‐BW is effective for increasing muscle mass, Watanabe et al reported that resistance training using body weight with slow speed movement and tonic force generation (3‐second eccentric, 3‐second concentric, and 1‐second isometric actions with no rest between each repetition) improved physical function and strength but not muscle mass. Holm et al reported that even with low‐load resistance training (15.5% of one repetition maximum), a long total contraction time is related to the activation of motor units, which increases muscle size and strength.…”
Section: Discussioncontrasting
confidence: 78%
“…Additionally, it was difficult for the elderly people to master the proper exercise technique of 7 kinds of exercises, and the research design was not a randomized controlled trial. In contrast, Watanabe et al 9 reported that SRT-BW and plyometric exercise significantly increased muscle strength but not muscle mass. Therefore, in this study, we conducted a randomized controlled trial to investigate whether 3 kinds of SRT-BW are effective for increasing muscle mass, muscle strength, and fat distribution in healthy elderly people.…”
Section: Introductionmentioning
confidence: 88%
“…reduction of all‐cause mortality) to gym‐based training . In this study, resistance exercise with body weight or rubber band followed a slow movement protocol . Some research groups have previously reported the effects of a resistance training programme using such as low movement protocol in a small sample of older participants .…”
Section: Discussionmentioning
confidence: 99%
“…Even for the elderly, it is clear that muscle strength can be reinforced by administering an appropriate program [21] [22], and it is expected that the effects of preventing the need for long-term care can be improved by specific interventions.…”
Section: Discussionmentioning
confidence: 99%